2022
DOI: 10.3389/fpsyg.2022.837996
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Job Stress, Psychological Adaptation and Internet Gaming Disorder Among Migrant Factory Workers in China: The Mediation Role of Negative Affective States

Abstract: Factory workers make up a large proportion of China’s internal migrants and may be highly susceptible to job and adaptation stress, negative affective states (e.g., depression and anxiety), and Internet gaming disorder (IGD). This cross-sectional study investigated the relationships between job stress, psychological adaptation, negative affective states and IGD among 1,805 factory workers recruited by stratified multi-stage sampling between October and December 2019. Structural equation modeling (SEM) was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…In other words, these intrapersonal factors may play as mediators or underlying mechanisms in explaining the relationships from higher socio-ecological level factors to individual IGD. For example, environmental and interpersonal stress and a lack of social support may cause maladaptive coping which in turn can increase the risk of IGD ( Cao et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, these intrapersonal factors may play as mediators or underlying mechanisms in explaining the relationships from higher socio-ecological level factors to individual IGD. For example, environmental and interpersonal stress and a lack of social support may cause maladaptive coping which in turn can increase the risk of IGD ( Cao et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…To enhance review, we additionally identified five pertinent articles from the references of the remaining studies, relevant meta-analyses, and reviews published recently. This adjustment brought the total number of articles under consideration to 22 [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Considering the rising incidence of STIs, WHO has proposed a Global Health Sector Strategy for STIs 2016-2021, which aims to end the public health problem of the STI epidemic by 2030, including reducing the incidence of gonorrhea by 90% globally (2018 global baseline) and in 80% of countries reducing congenital syphilis per 100,000 live births reduce incidence by more than 50 cases (2). Additionally, previous studies suggest that various interventions should increase HIV/STIs awareness and reduce HIV/STIs-related risk behaviors among factory workers in China because they are particularly vulnerable to infection (3)(4)(5). One key strategy to reduce the incidence of HIV/STIs is to increase awareness and attitudes toward risky sexual behaviors (6,7).…”
Section: Introductionmentioning
confidence: 99%